Alcohol consumption in tertiary education students - Reavley Nicola J; Jorm Anthony F; McCann Terence V; Lubman Dan I (BMC, 2011)
Abstract Background Heavy alcohol consumption among adolescents and young adults is an issue of significant public concern. With approximately 50% of young people aged 18-24 attending tertiary education, there is an opportunity within these settings to implement programs that target risky drinking. The aim of the current study was to survey students and staff within a tertiary education institution to investigate patterns of alcohol use, alcohol-related problems, knowledge of current National Health and Medical Research Council (NHMRC) guidelines for alcohol consumption and intentions to seek help for alcohol problems. Methods Students of an Australian metropolitan university (with staff as a comparison group) participated in a telephone interview. Questions related to knowledge of NHMRC guidelines, drinking behaviour, alcohol-related problems and help-seeking intentions for alcohol problems. Level of psychological distress was also assessed. Results Of the completed interviews, 774 (65%) were students and 422 (35%) were staff. While staff were more likely to drink regularly, students were more likely to drink heavily. Alcohol consumption was significantly higher in students, in males and in those with a history of earlier onset drinking. In most cases, alcohol-related problems were more likely to occur in students. The majority of students and staff had accurate knowledge of the current NHMRC guidelines, but this was not associated with lower levels of risky drinking. Psychological distress was associated with patterns of risky drinking in students. Conclusions Our findings are consistent with previous studies of tertiary student populations, and highlight the disconnect between knowledge of relevant guidelines and actual behaviour. There is a clear need for interventions within tertiary education institutions that promote more effective means of coping with psychological distress and improve help-seeking for alcohol problems, particularly among young men.